Client’s Collaborative Perception on the Therapeutic Relationship Regarding the Role of Psychotherapy in Selected Counselling and Training Centers in Rwanda - Birungi, Barbara; Safari, Ernest; Sessazi, Mukuru Alfred (Journal of Advanced Research in Humanities and Social Sciences; Vol 7 No 1 (2020): Journal of Advanced Research in Humanities and Social Science, 2020)
The general objective of the study was to examine clients’ collaborativeperceptions on the therapeutic relationship regarding the role of psychotherapy in Rwanda with selected counseling and trainingcenters. The study used descriptive and cross-sectional study designs. Statistics provided by the administrators at all the selected centers indicated that Lighthouse Counselling & Training Center received approximately 94 clients in a month, Solid Minds Counselling Center received approximately 63 clients in a month, and the University Counselling Center at Gashora Girls Academy received approximately 157 clients in a month. Hence, the total target population of the study was 314 clients attending therapy sessions in the selected counselling centers.Hence, the total target population for the study was 314 clients. The sample size (n = 176) of the study was determined using Slovin’s formula. Purposive and convenience sampling techniques were used. Primary data was collected from the study’s respondents using a research questionnaire and interview guide. Findings from the study suggested that 52.8% had a good collaborative therapeutic alliance.Respondents agreed with all the statements that; therapist listens attentively to issues and concerns (mean 4.38); therapist offered an environment that facilitated affective expression (mean 4.49); therapist offered an environment that facilitated deep, exploratory questioning (mean 4.15); therapist offered direct guidance and was always available to factor in any concerns arising (mean 4.26); the therapeutic sessions fostered self-understanding/insight (mean 4.17); my therapist adapts to my needs and goals (mean 4.23); and my therapist offers interpretative responses (mean 4.11). The study recommended that therapists should develop strategies aimed at fostering collaborative relationships by being able to understand the ability of a client to adopt to a treatment plan, involving them in the treatment decision-making process, and discussing any possibilities of therapist mistakes in the initial sessions and clients need to inform their therapists what they feel about the sessions in order to help them reframe the objectives of the counselling sessions as well as goals. How to cite this article:  Birungi B, Safari E, Sessazi MA et al. Client’s Collaborative Perception on the Therapeutic Relationship Regarding the Role of Psychotherapy in Selected Counselling and Training Centers in Rwanda. J Adv Res Humani Social Sci 2020; 7(1): 1-8.